Comparison of simulation methods for charged systems of slab geometry - Mazars, M.; Caillol, J.-M.; Weis, J.-J.; Levesque, D. (Condensed Matter Physics, 2001)
Using the specific model of a system of like charged ions confined between
two planar like charged surfaces, we compare the predictions for the energy
and density profile of four simulation methods available to treat the long
range Coulomb interactions in systems periodic in two directions but bound
in the third one. Monte Carlo simulations demonstrate unambiguously complete
agreement between the results obtained with these methods where
the potential between charges is solution of Poisson’s equation in the simulation
cell with adequate boundary conditions. The practical advantages
of the different methods are assessed. Користуючись специфічною моделлю систем однойменно заряджених іонів обмежених двома плоскими однойменно зарядженими поверхнями проведено порівняння енергії і профілю густини чотирьох
можливих методів комп’ютерного моделювання для врахування далекосяжних кулонівських взаємодій в системах періодичних за двома напрямками і обмежених за третім напрямком. Методи Монте-Карло показують повну однозначну узгодженість результатів отриманих цими методами, якщо потенціал між зарядами задовільняє
рівнянню Пуасона для симуляційної комірки з відповідними граничними умовами. Оцінено практичні переваги різних методів.